2022
DOI: 10.1161/atvbaha.122.317526
|View full text |Cite
|
Sign up to set email alerts
|

Different Metabolic Phenotypes of Obesity and Risk of Coronary Artery Calcium Progression and Incident Cardiovascular Disease Events: The CARDIA Study

Abstract: Background: To investigate whether obesity with or without metabolic syndrome is prospectively associated with coronary artery calcium (CAC) progression and incident cardiovascular disease events. Methods: A total of 1730 participants from the CARDIA study (Coronary Artery Risk Development in Young Adults) were included (age, 40.1±3.6 years; 38.3% men), who completed computed tomography of CAC at baseline (year 15: 2000–2001) and follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(91 reference statements)
0
6
1
Order By: Relevance
“…Obesity is known to increase the risk for CHD even among metabolically healthy individuals 11 . This may be due to several mechanisms, including increased oxidative stress and vascular calcification resulting from the activation of vascular bone morphogenetic protein 40,41 . In addition, adipose tissues release adipokines that can induce a proinflammatory effect, disrupting vascular homeostasis and promoting atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is known to increase the risk for CHD even among metabolically healthy individuals 11 . This may be due to several mechanisms, including increased oxidative stress and vascular calcification resulting from the activation of vascular bone morphogenetic protein 40,41 . In addition, adipose tissues release adipokines that can induce a proinflammatory effect, disrupting vascular homeostasis and promoting atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…vascular calcification resulting the activation of vascular bone morphogenetic protein. 40,41 In addition, adipose tissues release adipokines that can induce a proinflammatory effect, disrupting vascular homeostasis and promoting atherogenesis. Even MHO individuals have been found to have elevated levels of C-reactive protein and circulating proinflammatory monocytes, indicating the presence of inflammation.…”
Section: Notementioning
confidence: 99%
“…The CARDIA study included patients with several obesity phenotypes (with healthy and unhealthy metabolism). Its analysis has demonstrated the highest risk for coronary artery calcification (CAC) progression in obese subjects with unhealthy metabolism and the lowest risk in non-obese subjects [ 19 ]. Ageing is also considered the major risk factor of CVD.…”
Section: Diabesity and Cardiovascular Diseasementioning
confidence: 99%
“…Several studies have demonstrated that the presence of metabolic syndrome heightens the risk of stroke and myocardial infarction (10)(11)(12). Some studies have reported on the correlation between different metabolic phenotypes and the risk of cardiovascular disease, but the conclusions have not been consistent (13)(14)(15). This indicates that different metabolic types may have varying risks for cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%